What should be computed to understand and model brain function? : from robotics, soft computing, biology and neuroscience to cognitive philosophy - Kitamura, Tadashi, 1947- (FLSI soft computing series, 2001)
This volume is a guide to two types of transcendence of academic borders which seem necessary for understanding and modelling brain function. The first type is a technical transcendence needed to make intelligent machines such as a humanoid robot, an animal-like behaviour architecture, an interpreter of fiction, and an evolving learning machine. This technical erosion is conducted into areas such as biology, ethology, neuroscience and psychology, as well as robotics and soft computing. The second type of transcendence of cross-disciplinary boundaries cuts across scientific areas such as biology and cognitive science/philosophy, into comprehensive, less technical and more abstract aspects of brain function. These aspects enable us to know in what direction and how far an intelligent machine will go.